Effectiveness of information and communication technology on crime prevention in the Nigeria customs service (2018)
The study examined the effectiveness of Information and Communication Technology (ICT) in the prevention of crime by the Nigeria Customs Service. The study adopted the descriptive survey research design. A total of four hundred (400) customs officers were purposively drawn from the three (3) Area Commands in the South-West that share border with neighboring countries (Benin Republic and Republic of Togo). A questionnaire tagged “Perception of workers on the effectiveness of ICT in Crime Prevention in Nigeria Customs Service was developed and used lo collect data. Simple percentage, frequency counts, and Pearson Product-Moment Correlation were used in analyzing the data collected. Two research questions and one hypothesis (tested al 0.05 level of statistical significance) were raised. The hypothesis revealed a significant positive relationship between ICT and crime prevention r = (752), 0.000, P< .05. It was recommended that the NCS should further improve on the aspect of E-payment so as to completely eliminate the use of bribes to bring in contraband goods into the country. NCS should also improve further on the ASYCUDA++ in order to better simplify clearance of goods